Method for rapidly preparing Cf / SiC-HfC composite material
By using chemical vapor deposition process to prepare pyrolyzed carbon interface layer and solvent-free silicon carbide ceramic precursor adhesive film in the production of Cf/SiC-HfC composite materials, combined with molding and low-cycle PIP processes, the existing technology has been solved The problems of long production cycle and high cost achieve rapid preparation of low-cost and high-performance Cf/SiC-HfC composite materials.
Patent Information
- Application Number
- CN202411687615.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-02-14
AI Technical Summary
The long production cycle and high cost of existing Cf/SiC-HfC composites limit the reduction of cost of spacecraft. Especially in my country, the research on low-cost and high-performance ceramic composites is relatively basic, resulting in higher aerospace launch costs.
The pyrolytic carbon interface layer was prepared by chemical vapor deposition process, combined with the solvent-free silicon carbide ceramic precursor film and composited with the carbon cloth, and quickly prepared Cf/SiC-HfC composite material through molding process and low-cycle PIP process.
The rapid preparation of Cf/SiC-HfC composite materials is realized, which reduces production costs, simplifies the process flow, improves the density and performance of the material, and has good ultra-high temperature resistance, oxidation resistance and ablation resistance.
Smart Images

Figure CN119430974A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of special ceramic materials, in particular to a method for rapidly preparing C f / SiC-HfC composites. Background Art
[0002] C f / SiC-HfC composite materials are widely used in aerospace and other fields due to their advantages such as high hardness, high specific modulus, high specific strength, corrosion resistance and high temperature resistance.
[0003] However, C f / SiC-HfC composite materials have long production cycles and high costs, making the cost of aerospace vehicles extremely expensive. In recent years, developed countries such as Europe and the United States have been continuously reducing the cost of aerospace vehicles, which is mainly due to the fact that these countries have achieved low-cost, high-performance C f / SiC-HfC composites. However, in my country, the traditional fiber woven composites, ceramic precursor impregnation pyrolysis technology (PIP) or chemical vapor deposition (CVI) are still used. These technologies are costly and the performance of the prepared ceramic matrix composites is poor. Moreover, at present, the research on low-cost and high-performance ceramic composites in my country is still relatively basic. The launch cost of spacecraft is much higher than that of European and American countries. Therefore, there is an urgent need to develop a low-cost and high-performance C f / SiC-HfC composites.
[0004] In recent years, the method of adding solvent powder to polycarbosilane to prepare slurry, brushing carbon cloth, and then using molding process to prepare flat plate material, and then using 6-10 rounds of PIP to prepare C f / SiC-HfC composite materials. However, due to the presence of a large amount of solvent in the slurry, a large amount of solvent evaporates during the molding process. f A large number of defects are left inside the SiC-HfC composite material, so more than 6 rounds of PIP are required to complete its densification, which prolongs the process cycle of composite molding.
[0005] Therefore, it is very necessary to provide a method for rapidly preparing C with strong process applicability, simple preparation process, adjustable and controllable HfC powder addition amount and excellent mechanical properties. f / SiC-HfC composites. Summary of the invention
[0006] The purpose of the present invention is to provide a method for rapidly preparing C f / SiC-HfC composite material method to solve the problems in the background technology, the prepared C f / SiC-HfC ceramic matrix composites have broad application prospects in the aerospace field.
[0007] To achieve the above object, the present invention provides a method for rapidly preparing C f The method for preparing a SiC-HfC composite material comprises the following steps:
[0008] 1) placing the heat-treated carbon in a chemical vapor deposition furnace, and preparing a pyrolytic carbon interface layer on the surface of the carbon cloth by chemical vapor infiltration;
[0009] 2) mixing HfC powder, sintering aid, solid silicon carbide ceramic precursor, liquid silicon carbide ceramic precursor and organic solvent, removing the organic solvent after uniform dispersion by ultrasonication, preparing silicon carbide ceramic precursor film by coating machine, and compounding the film with carbon cloth with pyrolytic carbon interface to prepare carbon ceramic prepreg;
[0010] 3) Laying the carbon ceramic prepreg in a mold, applying pressure using a press, and curing by heating to prepare a carbon ceramic resin-based composite material;
[0011] 4) pressurizing the carbon ceramic resin-based composite material and pyrolyzing it at high temperature under an inert atmosphere to prepare a carbon ceramic composite material;
[0012] 5) The carbon ceramic composite material is subjected to pressure impregnation, pressure curing, and pyrolysis (PIP) in an inert atmosphere 1-2 times using a liquid silicon carbide ceramic precursor until the density of the composite material is 1.6-2.2 g / cm 3 , that is, the densified C f / SiC-HfC composites.
[0013] Preferably, in step 1), the thickness of the pyrolytic carbon interface layer is 0.3 μm-0.8 μm.
[0014] Preferably, in step 2), the amounts of HfC powder, sintering aid, solid silicon carbide ceramic precursor and liquid silicon carbide ceramic precursor used are 20-50 parts, 3-10 parts, 20-50 parts and 50-80 parts respectively by weight.
[0015] Preferably, in step 2), the particle size of the HfC powder is 1-3 μm.
[0016] Preferably, in step 2), the sintering aid is one of nano-scale Al2O3, MgO, ZrO2, Y2O3, CaO, and SiO2, and the organic solvent is n-hexane.
[0017] Preferably, in step 2), the solid silicon carbide ceramic precursor and the liquid silicon carbide ceramic precursor are both polycarbosilane and one of B and Si modified polycarbosilane.
[0018] Preferably, in step 2), the silicon carbide ceramic precursor film is solvent-free, meltable at 80-100°C, with a viscosity of 5Pa·S-50Pa·S and a viscosity within 1Pa·S at 120-150°C.
[0019] Preferably, in step 3), the pressurizing pressure of the press is 3-7 MPa, the curing temperature is 200° C.-350° C., and the pressurizing curing time is 2-6 h.
[0020] Preferably, in step 4), the pressurization pressure is 3-10 MPa, the high temperature cracking temperature is 1200-1600° C., and the time is 2-4 h.
[0021] Preferably, in step 5), the pressure of the pressurized impregnation is 3-5 MPa; the pressure of the pressurized curing is 3-5 MPa, the temperature of the pressurized curing is 180-250°C, and the time of the pressurized curing is 2-4 h; the temperature of the pyrolysis is 900-1200°C, and the time of the pyrolysis is 1-2 h.
[0022] Therefore, the invention provides a method for rapidly preparing C f The method of the SiC-HfC composite material has the following beneficial effects:
[0023] (1) Compared with traditional ceramic matrix composites, the added HfC powder content is controllable and the type is adjustable. f / SiC-HfC composite material has good ultra-high temperature resistance, oxidation resistance, and ablation resistance. The flexural strength at room temperature is 200-400MPa, the tensile strength is 300-400MPa, and the flexural strength at 1800℃ is above 100MPa. After 300S of oxyacetylene flame 1800-2200℃ test, the linear ablation rate is on the order of 10-3mm / s, which is close to zero ablation.
[0024] (2) The present invention adopts chemical vapor deposition process to prepare pyrolytic carbon interface layer on carbon cloth, uses solvent-free silicon carbide ceramic precursor film to prepare SiC transition matrix, and adopts precursor impregnation cracking process to seal the pores. The preparation process is simple and easy to operate, and greatly shortens the preparation cycle, reduces costs, and has strong applicability.
[0025] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 C prepared in Example 4 of the present invention f / SEM image of SiC-HfC composite material. DETAILED DESCRIPTION
[0027] The present invention is further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention. Any other changes, modifications, substitutions, combinations, simplifications made without violating the spirit and principle of the present invention should all be equivalent replacement methods and are included in the protection scope of the present invention. In addition, it should be understood that after reading the content of the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the claims attached to this application, and all belong to the scope of protection of the present invention.
[0028] Reference to "embodiment" herein means that the specific features, structures or characteristics described in conjunction with the embodiment may be included in at least one embodiment of the present application. The term "embodiment" appearing in various places in the specification does not necessarily refer to the same embodiment, nor does it particularly limit its independence or association with other embodiments. In principle, in the present application, as long as there is no technical contradiction or conflict, the various technical features mentioned in the embodiments can be combined in any way to form a corresponding implementable technical solution.
[0029] Unless otherwise defined, the technical terms used in this document have the same meanings as those generally understood by those skilled in the art to which this application belongs; the use of relevant terms in this document is only for describing specific embodiments and is not intended to limit this application.
[0030] Unless otherwise specified in the present invention, the reagents, instruments, and equipment used are those commonly used by technicians in this field.
[0031] Example 1
[0032] This embodiment provides a method for rapidly preparing C f / SiC-HfC composite material method, the specific steps are as follows:
[0033] (1) The carbon cloth treated at 1600°C for 2 h was placed in a chemical vapor deposition furnace, and a pyrolytic carbon interface layer was prepared on the surface of the carbon cloth by chemical vapor infiltration, with a thickness of 0.3 μm.
[0034] (2) 40 parts of 1 μm HfC powder, 5 parts of 50 nm MgO powder, 30 parts of solid polyborosilazane, 70 parts of liquid polyborosilazane and n-hexane were evenly dispersed by ultrasonic dispersion and the n-hexane was removed. A 0.4 mm thick silicon carbide ceramic precursor film was prepared by a coater at 80°C with a viscosity of 9.5 Pa·S. The film was then composited with a carbon cloth with a pyrolytic carbon interface at a composite temperature of 130°C and a viscosity of 107 mPa·S to prepare a carbon ceramic prepreg.
[0035] (3) 16 layers of carbon ceramic prepreg were laid in a mold, pressurized to 3 MPa using a press, heated to 250° C. and cured for 3 h to prepare a carbon ceramic resin-based composite material.
[0036] (4) The carbon ceramic resin-based composite material was pressurized to 4 MPa using a press and pyrolyzed at high temperature under Ar gas at a pyrolysis temperature of 1200°C for 2 hours to prepare a carbon ceramic composite material.
[0037] (5) The prepared carbon ceramic composite material is subjected to pressure impregnation of silicon carbide ceramic precursor at a pressure of 3 MPa, pressure curing at a pressure of 3 MPa, curing temperature of 200 ° C, curing time of 2 h, pyrolysis temperature of 900 ° C, time of 2 h, and 2 cycles to complete C f Densification of SiC-HfC composites.
[0038] The C prepared in this example f / SiC-HfC composite material density is 1.8g / cm 3 The bending strength at room temperature is 274MPa, the tensile strength is 315MPa, the bending strength at 1800℃ is 112MPa, and the line ablation rate is 2.5×10 -3 mm / s order of magnitude, close to zero ablation.
[0039] Example 2
[0040] This embodiment provides a method for rapidly preparing C f / SiC-HfC composite material method, the specific steps are as follows:
[0041] (1) The carbon cloth treated at 1200°C for 6 hours was placed in a chemical vapor deposition furnace, and a pyrolytic carbon interface layer was prepared on the surface of the carbon cloth by chemical vapor infiltration, with a thickness of 0.5 μm.
[0042] (2) 50 parts of 3 μm HfC powder, 7 parts of 50 nm ZrO2 powder, 20 parts of solid polycarbosilane, 80 parts of liquid polycarbosilane and n-hexane were evenly dispersed by ultrasonication and then the n-hexane was removed. A 0.35 mm thick silicon carbide ceramic precursor film was prepared by coating at 100°C with a viscosity of 6.5 Pa·S. The film was then compounded with a carbon cloth with a pyrolytic carbon interface at a compounding temperature of 140°C and a viscosity of 402 mPa·S to prepare a carbon ceramic prepreg.
[0043] (3) The carbon ceramic prepreg was layered in 23 layers in a mold, pressurized to 7 MPa using a press, heated to 300° C. and cured for 5 h to prepare a carbon ceramic resin-based composite material.
[0044] (4) The carbon ceramic resin-based composite material was pressurized to 8 MPa using a press and pyrolyzed at high temperature under nitrogen at a pyrolysis temperature of 1400°C for 3 hours to prepare a carbon ceramic composite material.
[0045] (5) The prepared carbon ceramic composite material is impregnated with a silicon carbide ceramic precursor at a pressure of 5 MPa, a pressure of 5 MPa for pressurized curing, a curing temperature of 180°C, a curing time of 4 h, a pyrolysis temperature of 1200°C, a time of 2 h, and a cycle of 1 round to complete C f Densification of SiC-HfC composites.
[0046] The C prepared in this example f / SiC-HfC composite material density is 2.0g / cm 3 The bending strength at room temperature is 312MPa, the tensile strength is 356MPa, the bending strength at 1800℃ is 132MPa, and the line ablation rate is 6.3×10 -3 mm / s order of magnitude, close to zero ablation.
[0047] Example 3
[0048] This embodiment provides a method for rapidly preparing C f / SiC-HfC composite material method, the specific steps are as follows:
[0049] (1) The carbon cloth treated at 1000°C for 6 hours was placed in a chemical vapor deposition furnace, and a pyrolytic carbon interface layer was prepared on the surface of the carbon cloth by chemical vapor infiltration, with a thickness of 0.7 μm.
[0050] (2) 45 parts of 2 μm HfC powder, 10 parts of 30 nm Al2O3 powder, 35 parts of solid polyborosilazane, 65 parts of liquid polyborosilazane and n-hexane were evenly dispersed by ultrasonication and then the n-hexane was removed. A 0.3 mm thick silicon carbide ceramic precursor film was prepared by a coater at 90°C with a viscosity of 5.5 Pa·S. The film was then composited with a carbon cloth with a pyrolytic carbon interface at a composite temperature of 120°C and a viscosity of 130 mPa·S to prepare a carbon ceramic prepreg.
[0051] (3) The carbon ceramic prepreg was layered in 15 layers in a mold, pressurized to 5 MPa using a press, heated to 350° C. and cured for 2 h to prepare a carbon ceramic resin-based composite material.
[0052] (4) The carbon ceramic resin-based composite material was pressurized to 10 MPa using a press and pyrolyzed at high temperature under Ar gas at a pyrolysis temperature of 1200°C for 2 hours to prepare a carbon ceramic composite material.
[0053] (5) The prepared carbon ceramic composite material is impregnated with a silicon carbide ceramic precursor at a pressure of 4 MPa, a pressure of 4 MPa for pressurized curing, a curing temperature of 180 ° C, a curing time of 2 h, a pyrolysis temperature of 1000 ° C, a time of 2 h, and a cycle of 1 round to complete the C f Densification of SiC-HfC composites.
[0054] The C prepared in this example f / SiC-HfC composite material density is 1.92g / cm 3 The bending strength at room temperature is 332MPa, the tensile strength is 307MPa, the bending strength at 1800℃ is 157MPa, and the line ablation rate is 7.5×10 -3 mm / s order of magnitude, close to zero ablation.
[0055] Example 4
[0056] This embodiment provides a method for rapidly preparing C f / SiC-HfC composite material method, the specific steps are as follows:
[0057] (1) The carbon cloth treated at 1350°C for 2 h was placed in a chemical vapor deposition furnace, and a pyrolytic carbon interface layer was prepared on the surface of the carbon cloth by chemical vapor infiltration, with a thickness of 0.6 μm.
[0058] (2) 20 parts of 1.5 μm HfC powder, 3 parts of 50 nm ZrO2 powder, 50 parts of solid polycarbosilane, 50 parts of liquid polycarbosilane and n-hexane were evenly dispersed by ultrasonication and the n-hexane was removed. A 0.45 mm thick silicon carbide ceramic precursor film was prepared by a coater at 95°C with a viscosity of 7.5 Pa·S. The film was then composited with a carbon cloth with a pyrolytic carbon interface at a composite temperature of 150°C and a viscosity of 95 mPa·S to prepare a carbon ceramic prepreg.
[0059] (3) The carbon ceramic prepreg was layered in 27 layers in a mold, pressurized to 7 MPa using a press, heated to 300° C. and cured for 3 h to prepare a carbon ceramic resin-based composite material.
[0060] (4) The carbon ceramic resin-based composite material was pressurized to 7 MPa using a press and pyrolyzed at high temperature under nitrogen at a pyrolysis temperature of 1500°C for 2 hours to prepare a carbon ceramic composite material.
[0061] (5) The prepared carbon ceramic composite material is impregnated with a silicon carbide ceramic precursor at a pressure of 4 MPa, a pressure of 3 MPa for pressurized curing, a curing temperature of 240 ° C, a curing time of 2 h, a pyrolysis temperature of 1200 ° C, a time of 2 h, and a cycle of 2 rounds to complete the Cf Densification of SiC-HfC composites.
[0062] The C prepared in this example f SEM images of / SiC-HfC composites are shown in Figure 1 As shown by Figure 1 It can be seen that the composite material prepared by this method has fewer pores and is denser.
[0063] Preparation of C f / SiC-HfC composite material density is 1.68g / cm 3 The bending strength at room temperature is 240MPa, the tensile strength is 365MPa, the bending strength at 1800℃ is 101MPa, and the line ablation rate is 4.5×10 -3 mm / s order of magnitude, close to zero ablation.
[0064] Example 5
[0065] This embodiment provides a method for rapidly preparing C f / SiC-HfC composite material method, the specific steps are as follows:
[0066] (1) The carbon cloth treated at 1000°C for 6 hours was placed in a chemical vapor deposition furnace, and a pyrolytic carbon interface layer was prepared on the surface of the carbon cloth by chemical vapor infiltration, with a thickness of 0.8 μm.
[0067] (2) 35 parts of 3 μm HfC powder, 8 parts of 50 nm MgO powder, 40 parts of solid polycarbosilane, 60 parts of liquid polycarbosilane and n-hexane were evenly dispersed by ultrasonic dispersion and the n-hexane was removed. A 0.75 mm thick silicon carbide ceramic precursor film was prepared by a coater at 80°C with a viscosity of 40.5 Pa·s. The film was then composited with a carbon cloth with a pyrolytic carbon interface at a composite temperature of 140°C and a viscosity of 805 mPa·s to prepare a carbon ceramic prepreg.
[0068] (3) Ten layers of carbon ceramic prepreg were laid in a mold, pressurized to 5 MPa using a press, heated to 250° C. and cured for 3 h to prepare a carbon ceramic resin-based composite material.
[0069] (4) The carbon ceramic resin-based composite material was pressurized to 6 MPa using a press and pyrolyzed at high temperature under Ar gas at a pyrolysis temperature of 1300°C for 2 hours to prepare a carbon ceramic composite material.
[0070] (5) The prepared carbon ceramic composite material is subjected to pressure impregnation of silicon carbide ceramic precursor at a pressure of 4 MPa, pressure curing at a pressure of 5 MPa, curing temperature of 180 ° C, curing time of 4 h, pyrolysis temperature of 900 ° C, time of 2 h, and a cycle of 2 rounds to complete C f Densification of SiC-HfC composites.
[0071] The C prepared in this example f / SiC-HfC composite material density is 1.87g / cm 3 The bending strength at room temperature is 364MPa, the tensile strength is 352MPa, the bending strength at 1800℃ is 202MPa, and the line ablation rate is 1.3×10 -3 mm / s order of magnitude, close to zero ablation.
[0072] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.
Claims
1. A rapid preparation method for C f / SiC-HfC composite material method, characterized in that, The specific steps include: 1) placing the heat-treated carbon in a chemical vapor deposition furnace, and preparing a pyrolytic carbon interface layer on the surface of the carbon cloth by chemical vapor infiltration; 2) mixing HfC powder, sintering aid, solid silicon carbide ceramic precursor, liquid silicon carbide ceramic precursor and organic solvent, removing the organic solvent after uniform dispersion by ultrasonication, preparing silicon carbide ceramic precursor film by coating machine, and compounding the film with carbon cloth with pyrolytic carbon interface to prepare carbon ceramic prepreg; 3) Laying the carbon ceramic prepreg in a mold, applying pressure using a press, and curing by heating to prepare a carbon ceramic resin-based composite material; 4) pressurizing the carbon ceramic resin-based composite material and pyrolyzing it at high temperature under an inert atmosphere to prepare a carbon ceramic composite material; 5) The carbon ceramic composite material is subjected to pressure impregnation, pressure curing, and cracking in an inert atmosphere for 1-2 times using a liquid silicon carbide ceramic precursor until the density of the composite material is 1.6-2.2 g / cm 3 , that is, the densified C f / SiC-HfC composites.
2. A rapid preparation method of C according to claim 1 f / SiC-HfC composite material method, characterized in that: In step 1), the thickness of the pyrolytic carbon interface layer is 0.3 μm-0.8 μm.
3. A rapid preparation method of C according to claim 1. f / SiC-HfC composite material method, characterized in that: In step 2), the amounts of HfC powder, sintering aid, solid silicon carbide ceramic precursor and liquid silicon carbide ceramic precursor used are 20-50 parts, 3-10 parts, 20-50 parts and 50-80 parts respectively by weight.
4. A rapid preparation method of C according to claim 1 f / SiC-HfC composite material method, characterized in that: In step 2), the particle size of the HfC powder is 1-3 μm.
5. A method for rapidly preparing C according to claim 1. f / SiC-HfC composite material method, characterized in that: In step 2), the sintering aid is one of nano-scale Al2O3, MgO, ZrO2, Y2O3, CaO, and SiO2; and the organic solvent is n-hexane.
6. A rapid preparation method of C according to claim 1. f / SiC-HfC composite material method, characterized in that: In step 2), the solid silicon carbide ceramic precursor and the liquid silicon carbide ceramic precursor are both polycarbosilane and one of B and Si modified polycarbosilane.
7. A rapid preparation method of C according to claim 1. f / SiC-HfC composite material method, characterized in that: In step 2), the silicon carbide ceramic precursor film is solvent-free, meltable at 80-100°C, with a viscosity of 5Pa·S-50Pa·S and a viscosity within 1Pa·S at 120-150°C.
8. A rapid preparation method of C according to claim 1. f / SiC-HfC composite material method, characterized in that: In step 3), the pressurizing pressure of the press is 3-7 MPa, the curing temperature is 200° C.-350° C., and the pressurizing curing time is 2-6 h.
9. A rapid preparation method of C according to claim 1 f / SiC-HfC composite material method, characterized in that: In step 4), the pressurization pressure is 3-10 MPa, the high temperature cracking temperature is 1200-1600° C., and the time is 2-4 h.
10. A method for rapidly preparing C according to claim 1. f / SiC-HfC composite material method, characterized in that: In step 5), the pressure of the pressurized impregnation is 3-5MPa; the pressure of the pressurized curing is 3-5MPa, the temperature of the pressurized curing is 180-250°C, and the time of the pressurized curing is 2-4h; the temperature of the pyrolysis is 900-1200°C, and the time of the pyrolysis is 1-2h.
Citation Information
Patent Citations
Preparation method for binary ceramic modified C / C composite material
CN106478120A
Carbon fiber-reinforced (carbon-) silicon carbide base-ultra-high temperature ceramic base compound material and production method thereof
CN109970460A
Densification preparation method of fiber-reinforced hafnium carbide ceramic-based composite material
CN111253171A
Preparation method of polycarbosilane blended resin hot-melt prepreg
CN113698774A
Ceramic-based continuous complex-phase adhesive film with high bonding strength and preparation method of ceramic-based continuous complex-phase adhesive film
CN114736613A
Cited By
Rapidly-densified high-toughness carbon-based composite material and preparation method thereof
CN121517229A